Uma análise sobre funções exponenciais e logarítmicas em livros didáticos à luz das habilidades propostas pela Base Nacional Comum Curricular - ASSUNÇÃO JÚNIOR , Reginaldo João (2019)
The Common National Curriculum Base (BNCC) has emerged to ensure students that their basic learning is developed and consolidated in basic education. The dissertation aims to analyze the BNCC skills regarding the study of exponential and logarithmic functions in mathematics books approved in PNLD 2018-2020: PAIVA (2015), IEZZI (2016) and SOUZA (2016), adopted in state schools of Maranhão. Concepts about mathematics are presented according to the National Curriculum Parameters (PCN's) and the BNCC, emphasizing its parameters for the analysis of the textbook. From the research data, it was observed that the ability EM13MAT305 is included in the referenced works, however for the EM13MAT405 there is no methodological mention for it. The other skills are seen by one or two works. Therefore, it is concluded that the works partially cover the skills, which are necessary for the teacher to have mastery of the contents covered in the pedagogical book. BNCC standards are important to ensure greater effectiveness in mathematics teaching.